Impact of Blockchain Technology: Benefits and Security Risk and Threats - Vlad-Andrei ROTUNDU (Informatică economică, 2022)
The accelerated dynamics of technological evolution has led to a reconfiguration of the security environment by addressing new vulnerabilities, risks and threats generated by the migration of risk-generating entities into cyberspace. These risks are also enhanced by the interest shown by criminal entities in technologies such as Blockchain, which are proving to be attractive in terms of existing functionalities. These changes in the security environment and, by extension, in the international economic environment, are challenges that require a proactive, sustainable and integrated approach. This article aims to analyze the impact of blockchain technology on society in terms of both the benefits and risks of exploiting this technology.